Research on the effects of machining paths and variable parameters of different passes on defects in multi-pass single-point incremental forming - Su, Chunjian (2024)
Multi-pass single-point incremental forming achieves large-angle part processing through multiple forming, and as the number of forming times increases, the number of forming defects on the workpiece also increases, significantly affecting the forming quality of the workpiece. This study focuses on multi-pass single-point incremental forming defects, investigating the effects of machining paths and different variable parameters on forming defects. It comprehensively analyses the effects of axial and radial compensation machining paths on forming defects through simulations and experiments. The results show that the greater the axial compensation, the more severe the wall thickness reduction and the fewer the sink mark defects. After radial compensation, the minimum wall thickness of the formed parts is reduced, and the larger the radial compensation, the more obvious the sink mark defects. The effects of variable pass angle, tool diameter, and layer feed rate on forming defects were also investigated. The results show that a decrease in the angle between passes reduces the minimum wall thickness of the workpiece. Furthermore, gradually increasing the tool diameter and decreasing the feed rate can increase the wall thickness of the workpiece; gradually decreasing the angle between passes increases the number of sink defects, whereas gradually increasing the tool diameter can reduce the number of sink defects. The sink defect is the smallest with the same layer feed rate. The effectiveness and accuracy of the simulation results have been verified through experiments, and this is of great significance for improving the forming accuracy of workpieces.